Robust and resilient control design for cyber-physical systems with an application to power systems - Quanyan Zhu; Basar, T. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
The tradeoff between robustness and resilience is a pivotal design issue for modern industrial control systems. The trend of integrating information technologies into control system infrastructure has made resilience an important dimension of the critical infrastructure protection mission. It is desirable that systems support state awareness of threats and anomalies, and maintain acceptable levels of operation or service in the face of unanticipated or unprecedented incidents. In this paper, we propose a hybrid theoretical framework for robust and resilient control design in which the stochastic switching between structure states models unanticipated events and deterministic uncertainties in each structure represent the known range of disturbances. We propose a set of coupled optimality criteria for a holistic robust and resilient design for cyber-physical systems. We apply this method to a voltage regulator design problem for a synchronous machine with infinite bus and illustrate the solution methodology with numerical examples.